Cultural and emotional factors of diabetic patients facing the disease - Galimberti Oliveira, María Cecilia (2020)
Objective. To know cultural and emotional factors of diabetic patients facing the disease. Methods. Methodology was qualitative, with ethnographic design. Sample comprised 10 patients, with type 2 diabetes, workers of Universidad Nacional Hermilio Valdizán de Huánuco to whom a semi-structured interview was applied, and data analysis was carried out with the program Atlas.ti. Results. The diabetic patient shows cultural differences that include the subject and their experience of illness. Illness limits patient’s social life. The important values found are settled fundamentally in family support and in feeling productive assuming responsibilities. Their cultural representations do not match their cultural practices since, in theory, they know what to do to adhere to treatment (diet, exercise, and take medicine) but in practice they do the opposite. Diabetic patients are influenced by their behavior due to the illness or condition: It constitutes a set of emotions, feelings and experiences that affect the patient's health. They associate the disease with the emotions and feelings they experience in their social life. These emotions transform your body and your life. The critical situations or strong impressions they experience will increase their blood pressure and also blood sugar levels. Conclusion. The cultural patterns of the diabetic patient, their ways of thinking and acts are determined by their living conditions and by a series of factors: sociocultural, economic and emotional.